2018
DOI: 10.3325/cmj.2018.59.149
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lactates in relation to gas analysis and acid-base status in patients with pulmonary embolism

Abstract: AimTo assess the prognostic value of lactate level for mortality in patients with pulmonary embolism (PE) and Pulmonary Embolism Severity Index (PESI) I-III and its independence of gas-analysis parameters and acid-base status.MethodsThis prospective observational study was conducted at the University Clinical Hospital Mostar from 2013 to 2017. On the first day after PE diagnosis, 1.5 mL of arterial blood was collected from 103 patients with PE. Partial pressure of oxygen in arterial blood, partial pressure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Logistic regression analysis of lactate values affecting PE related mortality in patients diagnosed with pulmonary embolism in the ED Galić K et al reported in their study that PE patients with a plasma lactate value >3 mmol/L had a very high mortality rate(9). In our study, the mortality risk in the group having lactate values ≥3 mmol/L was higher than the other two groups and the normotensive patient group.…”
supporting
confidence: 40%
“…Logistic regression analysis of lactate values affecting PE related mortality in patients diagnosed with pulmonary embolism in the ED Galić K et al reported in their study that PE patients with a plasma lactate value >3 mmol/L had a very high mortality rate(9). In our study, the mortality risk in the group having lactate values ≥3 mmol/L was higher than the other two groups and the normotensive patient group.…”
supporting
confidence: 40%
“…Previous study demonstrated that lactic acid has been linked to a greater risk of short-term mortality in patients with PE with a low-intermediate risk, independent of other gas-analytic parameters. 21 However, cancer patients were excluded from that study. The present study is the first, to our knowledge, to mention elevated lactic acid levels as a possible indicator of asymptomatic PE among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid has been reported to be associated with a high risk of mortality and adverse outcomes among patients with PE ( 23 ), and an increased in-hospital mortality in patients with acute PE ( 24 ). Furthermore, lactic acid has been linked to a greater risk of short-term mortality in patients with PE with a low-intermediate risk, independent of other gas-analytic parameters ( 25 ). In a recent study, Ząbczyk et al ( 26 ) reported that increased lactic acid levels were associated with increased neutrophil extracellular trap (NET) formation and prothrombotic fibrin clot features, with impaired plasma fibrinolytic potential in patients with acute PE.…”
Section: Discussionmentioning
confidence: 99%